RELIGIOSITY AS A MODERATOR OF THE RELATIONSHIP BETWEEN KNOWLEDGE AND PERCEPTION OF SAVING INTENTION - Faza Ainunnisa Affandy; Fani Firmansyah (Adisam Publisher, 2025)
The development of the Islamic banking industry in Indonesia is growing rapidly in line with increasing public awareness of Sharia-based finance. Malang, as a city with a large student population, is a potential market for Islamic banks. However, despite the majority of Indonesians being Muslim, students' interest in saving in Islamic banks still faces challenges. Therefore, this study aims to analyze the influence of knowledge and perception on students' interest in saving in Malang and to examine the role of religiosity as a moderating variable. This study used quantitative methods. Data were obtained by distributing questionnaires to students in Malang using a non-probability sampling technique. The sample size was set at 298 respondents, and data analysis was conducted using Partial Least Squares (PLS) with the assistance of SmartPLS software. The results show that knowledge and perception have a positive and significant effect on students' interest in saving in Islamic banks. However, religiosity was not proven to moderate the influence of knowledge or perception on interest in saving. This finding indicates that students' decisions to save are more influenced by rational considerations regarding Islamic banking products than by religiosity alone.